Analisis Linearitas Keluaran Radiasi pada X-Ray Mobile dengan Menggunakan Piranha - Nur Mukminah R; Iswadi Iswadi; Ihsan Ihsan Ihsan (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2014)
The research was conducted on the linearity of the output radiation in the mobile X-ray by using Piranha. This study aimed to measure the radiation dose exposure, to determine the relationship between the increase in the voltage of the radiation dose exposure and increase the tube current to the radiation dose exposure, as well as to analyze the radiation output and linearity of the output radiation. Data collection was conducted at the Dr. Tadjuddin Chalid Hospital Makassar in radiological installation. In this study the variables that measured the radiation dose and exposure variables that change the tube current and voltage. The data obtained and analyzed to calculate the value of the output radiation and radiation output linearity in the X- ray mobile. The analysis showed that the X-ray mobile with GE brand that are in radiological installation Dr. Tadjuddin Chalid Hospital has good linearity.